2018
DOI: 10.1016/j.ajo.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Content and Distribution in Endothelial Keratoplasty Tissue Determines Direction of Scrolling

Abstract: This pattern of elastin distribution in DM explains why DMEK and PDEK tissues always scroll with the EC outside. This behavior is not influenced by the EC. High elastin content and uniform distribution in the PDL suggest a structural difference from the posterior stroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
23
0
3
Order By: Relevance
“…90 95-97 Donor graft insertion and unfolding Upon separation from the posterior stroma, a free-floating DM has a natural tendency to adopt a scrolled-configuration with its endothelium on its outer surface. 98 This consistent 'endotheliumout' directional scrolling of DMEK graft tissues has been attributed to the elastin distribution within the DM-anterior dense band of elastin in the DM gives rise to a greater elasticity in its anterior compared to its posterior surface. 98 It makes intracameral graft unfolding one of the most technically demanding stages in DMEK surgery.…”
Section: Donor Graft Harvestingmentioning
confidence: 90%
See 1 more Smart Citation
“…90 95-97 Donor graft insertion and unfolding Upon separation from the posterior stroma, a free-floating DM has a natural tendency to adopt a scrolled-configuration with its endothelium on its outer surface. 98 This consistent 'endotheliumout' directional scrolling of DMEK graft tissues has been attributed to the elastin distribution within the DM-anterior dense band of elastin in the DM gives rise to a greater elasticity in its anterior compared to its posterior surface. 98 It makes intracameral graft unfolding one of the most technically demanding stages in DMEK surgery.…”
Section: Donor Graft Harvestingmentioning
confidence: 90%
“…98 This consistent 'endotheliumout' directional scrolling of DMEK graft tissues has been attributed to the elastin distribution within the DM-anterior dense band of elastin in the DM gives rise to a greater elasticity in its anterior compared to its posterior surface. 98 It makes intracameral graft unfolding one of the most technically demanding stages in DMEK surgery. In particular, scrolls formed are often tighter in younger donors, and thus unfolding is thought to be even more challenging in these circumstances.…”
Section: Donor Graft Harvestingmentioning
confidence: 90%
“…We note that in this study by Mohammed et al 1 a band of homogenous elastin immunofluorescence was identified above Descemet's membrane. We would be interested to know if the authors examined the elastin concentration between the posterior peripheral and central regions and, if so, were any differences detected?…”
supporting
confidence: 44%
“…We welcome the recent publication by Mohammed et al 1 that demonstrates the surgical implications of the corneal elastic system in scrolling in endothelial keratoplasty. We have pioneered the characterisation of the corneal elastic system in normal human 2 , keratoconic 3 corneas and in knock-out mouse models of Marfan's Syndrome.…”
mentioning
confidence: 89%
“…Zusätzlich zu Verbesserungen der Operationstechnik wäre es daher attraktiv, das Verhalten der Spenderlamelle aktiv zu beeinflussen und zu standardisieren. Mohammed et al zeigten 2018, dass die Rollung der Spenderlamelle durch Elastase komplett aufgehoben werden kann [8]. Eine komplette Degradation der Elastinfasern erachten wir im Hinblick auf eine langfristige Transplantatanlage jedoch als unvorteilhaft.…”
Section: Ergebnisseunclassified